Analisis Perbandingan Konsep Nilai Tukar Uang dalam Perspektif Ekonomi Islam dan Konvensional - Neti Hasaroh; Azka Najwa Ramadhani; Selvira Zahrani; Suci Hayati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Exchange rates play an important role in the global economy. In the conventional system, exchange rates are determined by market mechanisms that can cause economic instability due to speculation and currency fluctuations. In contrast, Islamic economics emphasizes stability, fairness, and the prohibition of speculative practices (gharar) in transactions. This study aims to compare the concept of exchange rates between Islamic and conventional economic systems. The method used is a literature study with a qualitative approach, using Islamic and conventional economic literature sources. The results of the analysis show that the exchange rate system in Islamic economics emphasizes stability and fairness through the support of intrinsic value and the avoidance of speculation, while the conventional system tends to be influenced by free market forces that are vulnerable to uncertainty. In conclusion, the Islamic approach to exchange rates offers a more stable and ethical alternative in maintaining economic balance.